Digital Empowerment of Women: The Role of the Internet in an Online University Setting - Sama Nasrati; Dina Khalil; Lima Ahmadi; Tamanna Quraishi (Tinta Emas Institute, 2024)
This study explores the impact of digital empowerment on female students in online university settings, focusing on internet connectivity, digital tools, and barriers to success. Using a survey distributed through Google Forms, we collected responses from 120 female participants across four faculties: Medical, Economics, Computer Science, and Education. The purpose was to assess how reliable internet access influences academic performance and engagement, evaluate the effectiveness of digital resources for professional skill development, and identify obstacles affecting women's participation. Results revealed that reliable internet access significantly enhances academic performance and engagement. Digital tools were highly rated for their effectiveness in skill development and career advancement. However, technological limitations and socio-economic factors were identified as major barriers. The findings suggest that while online universities offer valuable opportunities, addressing technological and socio-economic challenges is crucial for maximizing their benefits. Recommendations include improving internet infrastructure and providing targeted support to overcome socio-economic barriers. Future research should explore the longitudinal effects of digital empowerment initiatives and their impact on long-term academic and career outcomes for women.